2020
DOI: 10.1007/s13755-020-00110-y
|View full text |Cite
|
Sign up to set email alerts
|

Local feature descriptors based ECG beat classification

Abstract: ECG beat type analysis is important in the detection of various heart diseases. The ECG beats give useful information about the status of the monitored heart condition. Up to now, various artificial intelligence-based methods have been proposed for ECG based heart failure detection. These methods were generally based on either time or frequency domain signal processing routines. In this study, we propose a different approach for ECG beat classification. The proposed approach is based on image processing. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The comparison with other studies in the literature is not feasible since the selection of heartbeats, patients, or the classes to discriminate differs from one paper to another, in many of them, the choice seems to be made ad hoc. As far as we know, this is the first time that this milestone has been achieved for the QT database, since other authors consider specifically selected sets of patients of a much smaller size (see 27,32 and references therein). Moreover, a complete analysis is provided in the Supplementary Information including, specific-patient plots and statistics for the main FMM ecg parameters.…”
Section: Resultsmentioning
confidence: 92%
“…The comparison with other studies in the literature is not feasible since the selection of heartbeats, patients, or the classes to discriminate differs from one paper to another, in many of them, the choice seems to be made ad hoc. As far as we know, this is the first time that this milestone has been achieved for the QT database, since other authors consider specifically selected sets of patients of a much smaller size (see 27,32 and references therein). Moreover, a complete analysis is provided in the Supplementary Information including, specific-patient plots and statistics for the main FMM ecg parameters.…”
Section: Resultsmentioning
confidence: 92%
“…Herein, we adopted Sobel operators to detect the edges and reduce the noise of the image. The Sobel operators can be defined as follows: where Sobel x and Sobel y represent the horizontal operator and the vertical operator individually [ 32 ]. Then, the first-order differential Sobel operator is utilized to convolute the given image as follows: where G x denotes the convolution of picture F in the x -axis direction, where G y denotes the convolution of image F in the y -axis direction.…”
Section: Methodsmentioning
confidence: 99%
“…where Sobel x and Sobel y represent the horizontal operator and the vertical operator individually [32]. Then, the firstorder differential Sobel operator is utilized to convolute the given image as follows:…”
Section: Position-specific Scoring Matrix (Pssm)mentioning
confidence: 99%
“…Ongoing advancements in artificial intelligence (AI) have been implemented in numerous industries, including the education and medical field. According to numerous studies [1][2][3], AI has shown the ability to outperform humans and information systems at most cases [4][5][6][7][8]. It is a mechanical, electrical, and chemical organism that constitutes the human body [5].…”
Section: Introductionmentioning
confidence: 99%
“…Automated systems have a difficult time spotting anomaly. External noise and the body response to different physical conditions are examples of this [6][7][8].…”
Section: Introductionmentioning
confidence: 99%